MCAVIARFLORA OF THE ORAL CAVITY AND FEATURES OF INFLAMMATION OF THE RESPIRATORY TRACT IN PATIENTS WITH BRONCHIAL ASTHMA IN COMORBIDITY WITH RAPIDLY PROGRESSIVE PERIODONTITIS - Махкамова О.А. (Journals Park Publishing, 2023)
Evaluation of indicators of microbiological, clinical and respiratory status in the group of patients with rapidly progressing periodontitis in combination with bronchial asthma revealed that in patients the indicators of physical condition and ventilation capacity of the lungs were reduced, and the emotional state was tense compared to the group of healthy individuals.
Keywords: bronchial asthma, rapidly progressingperiodontitis, microbiological status, clinical status, tolerance to physical activity, emotional state, respiratory dysfunction.